1985
DOI: 10.1159/000166918
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Cyanide Intoxication with Hemodialysis

Abstract: A dramatic response was noted in a patient at our hospital who received hemodialysis therapy for severe acidosis secondary to an unknown toxin, subsequently identified as cyanide. We were unable to find any information concerning the hemodialysis clearance and extraction ratio of cyanide; thus, we studied the effect of hemodialysis in dogs receiving a constant infusion of cyanide with and without a simultaneous infusion of thiosulfate. The hemodialysis clearance of cyanide in the presence of thiosulfate was 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Hemodialysis has been advocated in some cases of cyanide toxicity; it would be particularly beneficial in the face of worsening acidosis and failing renal function, which would cause thiosulfate to accumulate and induce its own additional toxicity. 65…”
Section: Cyanide Is Extremely Quick To Act and There Is Often Limitementioning
confidence: 99%
“…Hemodialysis has been advocated in some cases of cyanide toxicity; it would be particularly beneficial in the face of worsening acidosis and failing renal function, which would cause thiosulfate to accumulate and induce its own additional toxicity. 65…”
Section: Cyanide Is Extremely Quick To Act and There Is Often Limitementioning
confidence: 99%
“…One animal study found that the haemodialysis clearance of cyanide is increased in the presence of thiosulphate, with a clearance of 38.3±5.4 mL/min and an extraction ratio of 0.43±0.06. 11 In retrospect, this case raises interesting points and further questions. It reinforces the importance of decontamination following poisoning with an unknown substance.…”
Section: Haemodialysis Treatmentmentioning
confidence: 89%
“…We have recently reported the effectiveness of hemodialysis in cyanide poisoning (54). At first glance, this appears to be an unlikely mode of therapy for cyanide toxicity for two reasons: first, the lethal effects of cyanide are related to its intracellular action on metabolism; second, the renal clearance of cyanide is virtually zero.…”
Section: C) Hemodialysismentioning
confidence: 99%
“…When a constant infusion of KCN was given to anephric animals an increase in the lethal dose resulted when hemodialysis was used concomitantly. The hemodialysis clearance of cyanide was found to be "" 40 ml/min and the extraction ratio was 0.43 (54). We reasoned that as an intracellular toxin, maneuvers forcing cyanide from inside the cell into the extracellular fluid should be even more effective in preventing mortality.…”
Section: C) Hemodialysismentioning
confidence: 99%